Homophily and Polarization in Twitter Political Networks: A Cross-Country Analysis - Esteve-Del-Valle, Marc (2022)
Homophily, the tendency of people to have ties with those who are similar, is a fundamental pattern to understand human relations. As such, the study of homophily can provide key insights into the flow of information and behaviors within political contexts. Indeed, some degree of polarization is necessary for the functioning of liberal democracies, but too much polarization can increase the adoption of extreme political positions and create democratic gridlock. The relationship between homophilous communication ties and political polarization is thus fundamental because it affects a pillar of democratic regimes: the need for public debate where divergent ideas and interests can be confronted. This research compares the degree of homophily and political polarization in Catalan MPs’ Twitter mentions network to Dutch MPs’ Twitter mentions network. Exponential random graph models were employed on a one-year sample of mentions among Dutch MPs (N = 7,356) and on a one-year, three-month sample of mentions among Catalan MPs (N = 19,507). Party polarization was measured by calculating the external–internal index of both Twitter mentions networks. Results reveal that the mentions among Catalan MPs are much more homophilous than those among the Dutch MPs. Indeed, there is a positive relationship between the degree of MPs’ homophilous communication ties and the degree of political polarization observed in each network.